Activated coagulation factors in human malignant effusions and their contribution to cancer cell metastasis and therapy - Gieseler, Frank; Lühr, Inke; Kunze, Thomas; Mundhenke, Christoph; Maass, Nicolai; Erhart, Tobias; Denker, Momme; Beckmann, Dennis; Tiemann, Markus; Schulte, Christoph; Dohrmann, Peter; Cavaillé, Françoise; Godeau, François; Gespach, Christian (Thrombosis and Haemostasis, 2007)
We have shown that the thrombin G-protein coupled receptors (GPCR) designated as protease-activated receptors (PAR-1) are expressed in primary cancer cells isolated from peritoneal and pleural malignant effusions. Here, our main goal was to evaluate several coagulation and thrombin activation effectors and markers in a series of 136 malignant effusions from cancer patients with gastrointestinal, lung and mammary carcinomas. All these patients present a highly activated coagulation system in blood and their malignant effusions, as indicated by high levels of prothrombin F1.2 fragments and D-dimers. Notably, we detected in the effusions all the coagulation factors of the tissue factor pathway inducing thrombin activation, namely factorsVII, V, X and II, as well as high VEGF levels and IGF-II in mature and precursor forms. Fibrin clot formation also correlated with higher levels of free ionized calcium (iCa), suggesting that iCa and its binding protein albumin are regulatory factors for fibrinogenesis in effusions. Consequently, thrombin,VEGF and IGFII appear to converge in the promotion of survival and invasivity of the metastatic cancer cells from blood to the malignant effusions. Thus, we add new insights on the interconnections between blood coagulation disorders in cancer patients and thrombin activation in malignant effusions, including their functional interaction with PAR in metastatic cancer cells. Based on these data we propose to counteract the metastatic cascades by targeted invalidation of key effectors of the coagulation system. Therefore, potential therapeutic approaches include the application of thrombin protease inhibitors, VEGF-blocking antibodies, and drugs targeting the VEGF and thrombin signaling pathways, such as tyrosine kinase or GPCR inhibitors.
Keywords: Thrombin; PAR-1; chemoresistance; invasion and survival